Studi al-Qur’an dan Hadits Mengenai Konsep Tarbiyah Iradah dalam Konsepsi Manajemen Sumber Daya Manusia (MSDM) - Aan Eko Khusni Ubaidillah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The lack of interest of the community in choosing Islamic education institutions is actually not because there has been a shift in Values â??â??or religious ties that are starting to fade, but because most existing Islamic education institutions are less promising in the future and less responsive to current and future demands and demands. In fact, there are at least three things that are considered by the community in choosing educational institutions, namely Values â??â??(religion), social status and ideals. The purpose of this article is to discuss the conception of Human Resource Management in students, especially related to Tarbiyatul Iradah. From the description that has been presented about the Study of the Qur'an and Hadith regarding the tarbiyah Iradah concept in the conception of Human Resource Management (HRM), it can be concluded as follows: 1) High quality human resources are resources that are able to create not only comparative value, but also innovative-generative competitive value using the highest energy such as intelligence, creativity, and imagination. 2) HR management that is effective and efficient towards our human beings, must go through four basic steps, namely; First, awareness that humans are servants of Allah SWT (Abdullah) and at the same time are His caliphs on earth; Secondly, as His caliph, every action must be based on the concept of being fair and not tyrannizing anyone; Third, synchronization between organizational goals and individual HR goals, namely Allah SWT, and; Fourth, the reference in human resource management is the character of the Prophet (Siddiq, Amanah, Fathanah, and Tabligh) 3) Tarbiyah as an effort in educating humans with the knowledge carried out by educators on the physical and spiritual development of students towards the formation of the main personality obedient to God, virtuous noble character, high knowledge and physical and spiritual health. Tarbiyah elements; a) Understanding and appreciation of Islam, b) Growth, Care and maintenance of faith, c) Growth of potential and talent so that it becomes a skill, d) The existence of stages (marhaliyah)